Populism and Euroscepticism in the Czech Republic: Meeting Friends or Passing By? - Petr Kaniok; Vlastimil Havlík (Romanian Journal of European Affairs)
Euroscepticism and populism, however defined, are often taken as two sides of the same coin, both in public discourse and academic debates. This paper challenges this common wisdom by analysing the case of the Czech Republic. Reviewing the EU related press releases produced by either Eurosceptic or Populist Czech parties, covering a six months period in 2014, the paper reveals to what extent there is a match between ‘Euroscepticism’ and ‘Populism’. As for the main results, the paper identifies that a) there is not a positive correlation between these two phenomena in the Czech Republic, and b) Euroscepticism seems to be inspired by Populism more than Populism draws from Euroscepticism in the Czech Republic.